Factors Driving the Interest of the Community in Caressing Used Goods: Case Study of the Sambu Medan Tax Shopping Center - Nazmi Najiha; Sri Herlina (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2025)
Interest is defined as a strong inclination or passion towards a particular desire, often manifesting as a longing to acquire specific items, such as clothing or second-hand goods, to fulfil personal needs and desires. This study aims to identify the factors influencing consumer interest in purchasing second-hand goods in Pajak Sambu, Medan City. Employing a qualitative research approach from a descriptive perspective, data were collected through direct interactions with consumers, including interviews and observations conducted at the research site. The study engaged six respondents to gather insights. The findings reveal several key factors that drive consumer interest in second-hand purchases: price, quality, brand, social influences, and style